UTILIZATION OF FINANCIAL TECHNOLOGY IN INCREASING THE INCOME OF MSMEs IN INDONESIA - Luqmanu Hakiem Ajuna; Alfitra Paputungan; Muhamad Ichksanul; A. Mokoagow; Silvana Masita Lestari; Rahmat Labatjo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The use of technology in the business sector has evolved into a requirement that cannot be disputed in order to support the efficient operation of corporate activities. Identifying current customer demands is a quick and efficient service. Today's technological advancements, including financial technology, present certain opportunities to business actors. The purpose of this study is to determine the role of financial technology in increasing MSME income. In this investigation, descriptive and qualitative data are analyzed. Secondary data from documents, the Central Bureau of Statistics (BPS), the Indonesian Ministry of Cooperatives, and SMEs are used in the methodology. The authors of this study used a triangulation method. In this study, the analysis processes included data reduction, data display, and, finally, conclusion-making. According to the study's findings, Fintech holds new promise for the growth of MSMEs in Indonesia. Capital and financing issues, as well as the difficult nature of the capital acquisition procedure, can be resolved with the assistance of the fintech loan program. Keywords: Financial Technology, MSMEs, Utilization, Income